ONLINE CREATIVE WRITING TRAINING FOR STUDENTS IN KEMLOKO VILLAGE, BLITAR REGENCY - Dwi Handayani; Trisna Kumala Satya Dewi; Bramantio (Jurnal Layanan Masyarakat (Journal of Public Services), 2022)
The ability to write as a form of proficiency in a variety of literature is a very important form of writing for students in schools in Kemloko Village. It is assumed that as intellectuals, they must have skills and master the language in a variety of literature. As a form of concern and service to the village community assisted by the Indonesian Language and Literature Study Program, it is necessary to hold these activities to create a young generation who is ready to face the progress of the times in the era of globalization. Thus, the Indonesian Language and Literature Study Program held the creative writing activity as an alternative step to prepare the younger generation who are ready to face the future by proficiently writing and reading. The activity was carried out online as well as an anticipation to break the chain of the spread of Covid-19. Furthermore, to support these activities, good cooperation is needed between the Indonesian Language and Literature Study Program, the Faculty of Cultural Sciences, Airlangga University with the Blitar Regency PORBUDPAR Service, and the MI School Committee and Kemloko Village Village. This strategy can create positive synergies by forming writing groups so that these activities can be applied in a structured and sustainable manner by producing a collection of interesting and quality poems and short stories even though they are online. Furthermore, the collection of students' writings will be made into a collection of books that have an ISBN and can be distributed to various levels of society.